Linfoma primario del sistema nervioso central en un paciente inmunocompetente - Málaga-Zenteno, José (2012)
Primary central nervous system lymphoma (PCNSL) constitutes 2% of extranodal lymphomas and 0,3%-1,5% of all intracranial neoplasms in immunocompetent patients, being more frequent after the sixth decade of life. We report a case of a 76 year-old man with no antecedents who started his disease with march instability, difficulty to move left side of his body with brachial predominance, holocraneal headache and dizziness. He arrived at emergency with Glasgow 14 and right eyelid ptosis. He had left sided hemiparesis and hypoesthesia with crural predominance and occasional disorientation. Brain computed tomography (CT) showed a contrastenhanced image in the right frontoparietal region with both extra- and intra-cranial components, cerebral edema and middle line deviation. Craniotomy and biopsy of the tumor resulted in diffuse large B cell lymphoma of the central nervous system. The patient was HIV negative. Other primary tumor and metastasis were discarded. He was treated with ‘CHOD/BVAM’ regimen and radiotherapy. He evolved favorably. No tumor was found in the post treatment brain MRI.